A PSYCHOLINGUISTIC STUDY ON COMPREHENSION DISORDER OF THE SCHIZOPHRENIC MAIN CHARACTER IN A BEAUTIFUL MIND MOVIE - Nugroho, Sumitro Agung (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research focuses on analyzing comprehension disorder of the schizophrenic character in A Beautiful Mind movie. Language disorder is a brain damage which causes the patient difficult to communicate with others. Comprehension disorder affects the brain's ability to understand, remember, and process information. People with schizophrenia disease often suffer terrifying symptoms such as hearing voices which are not heard by anyone else. They may believe that others are reading and controlling their minds. This research uses descriptive qualitative which describes language disorder and attempts to explore the application of sentence form as language disorder on language comprehension in schizophrenic utterances which are spoken by John Nash. The data are analyzed by classifying and analyzing the data into kinds of comprehension disorder and contexts by using Ginsberg theory. The finding of this research shows that the schizophrenic character of a Beautiful Mind movie has troubles in his language, especially in the language comprehension. His comprehension disorder is influenced by his delusion and hallucination. There are nine types of comprehension disorder that are shown in the dialogues; they are derailment, flight of ideas, word salad, irrelevant answer, blocking, retardation, perseveration, pressure of speech and circumstantiality. Three kinds of comprehension disorder which are not used by the schizophrenic character are clang association, neologism and incoherent.